Quantitative Comparison between the Smartphone Based Experiments for the Gravity Acceleration Measurement at Home - Marco Anni (MDPI AG, 2021)
Smartphones are currently proposed as potential portable laboratories to perform a wide variety of physical experiments for teaching purpose. However, the frequent lack of clarity about the ease of replication of the experiments and on their accuracy often limits their effective use. In this work we deeply compare several smartphone-based experiments to determine the gravity acceleration g by only using cheap materials easily available at home. The experiment and the data analysis complexity are progressively increased, starting from fast and easy to replicate methods. The advantages and possible limits of all the methods are deeply discussed in order to allow an evaluation of the most suitable method for any particular teaching scenario.